2016
DOI: 10.1007/s11096-016-0392-4
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization review of cephalosporins in a secondary care hospital in United Arab Emirates

Abstract: Background Cephalosporins are one of the most commonly used antibiotics in United Arab Emirates (UAE). Few studies have been carried out to evaluate the antibiotic utilization pattern in UAE in spite of the obvious increase in cephalosporins resistance during the past decade. Objective To assess the prescriptions pattern of cephalosporins among physicians at a secondary care hospital in Ras Al Khaimah, UAE. Method This observational prospective study was carried out during October 2013 to April 2014. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Seven (3.5 %) different ADRs linked to cephalosporin use were observed ranging from oral thrush to clostridium difficile infection. The 3 generation cephalosporin was commonly prescribed by parenteral route[12]. Our study is in complete agreement with the above study that states that ceftriaxone is the most commonly used drug in Saudis (86.7%) & in above study it was 81.1%.…”
supporting
confidence: 92%
“…Seven (3.5 %) different ADRs linked to cephalosporin use were observed ranging from oral thrush to clostridium difficile infection. The 3 generation cephalosporin was commonly prescribed by parenteral route[12]. Our study is in complete agreement with the above study that states that ceftriaxone is the most commonly used drug in Saudis (86.7%) & in above study it was 81.1%.…”
supporting
confidence: 92%
“…8,9,23 Similar results were obtained from various studies. 7,19,24,27,28 But it was quite different from the results of a study conducted by Kaliamoorthy et al, in a tertiary care hospital, in which ceftriaxone was ranked third in terms of utilization rate (19.5%) following cefixime (32.7%) and cefotaxime (31.3%). 17 The use of cephalosporins was found to be high for the treatment of RTIs.…”
Section: Discussionmentioning
confidence: 60%
“…This result is in agreement with the results of various other studies that were reported. 5,7,24 Another similar study conducted by Jonathan et al shows higher usage of 3GCs (95.85%), whereas a study conducted in a teaching hospital in Nepal shows a low use of 3GCs. 18,25 This higher use may be due to its broad spectrum of activity against most of the bacterial species, responsible for causing infections, especially against gram-negative microorganisms as well as the routine availability of these drugs in this setup.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations